Puberty is a Critical Period for Vomeronasal Organ Mediation of Socio-sexual Behavior in Mice - Cross, Sarah K. J.; Martin, Yellow H.; Salia, Stephanie; Gamba, Iain; Major, Christina A.; Hassan, Suhail; Parsons, Katelyn A.; Swift-Gallant, Ashlyn (Frontiers in Behavioral Neuroscience, 2021)
Genetic disruption of the vomeronasal organ (VNO), an organ responsible for pheromone processing, drastically alters socio-sexual behavior in mice. However, it is not known whether the VNO has a role during the pubertal organizational period, when sex-typical socio-sexual behaviors emerge, or if disruption of the organ in adulthood is sufficient to alter socio-sexual behavior. To bypass the lifelong VNO disruption of genetic knockout models, we surgically ablated the VNO of male and female mice either during the peripubertal period (postnatal day [PND] 28-30) or adulthood (PND 58-60), with sham controls at both ages. We ruled out anosmia via the buried food test, and assessed sexual odor preferences by simultaneously exposing mice to same- and opposite-sex soiled-bedding. We then measured territorial aggression with the resident-intruder paradigm, and assessed sexual behavior in response to an encounter with an estrus-induced female. Neural activity approximated by FOS-immunoreactivity along the VNO-accessory olfactory pathway was measured in response to opposite-sex odors. We found that peripubertal VNO ablation decreased sexual odor preferences and neural activity in response to opposite-sex odors, and drastically reduced territorial aggression in male mice. Conversely, adult VNO ablation resulted in subtle differences in sexual odor preferences compared with sham controls. Regardless of VNO condition, mice displayed sex-typical copulatory behaviors. Together, these results suggest that puberty is a critical period in development whereby the VNO contributes to the sexual differentiation of behavior and neural response to conspecific odors.